Biochemical Characterization of a Novel Bacterial Laccase and Improvement of Its Efficiency by Directed Evolution on Dye Degradation - Dai, Shuang; Yao, Qian; Yu, Gen; Liu, Shan; Yun, Jeonyun; Xiao, Xiong; Deng, Zujun; Li, He (Frontiers in Microbiology, 2021)
Laccase is a copper-containing polyphenol oxidase with a wide range of substrates, possessing a good application prospect in wastewater treatment and dye degradation. The purpose of this research is to study the degradation of various industrial dyes by recombinant laccase rlac1338 and the mutant enzyme lac2-9 with the highest enzyme activity after modification by error-prone PCR. Four enzyme activities improved mutant enzymes were obtained through preliminary screening and rescreening, of which lac2-9 has the highest enzyme activity. There are four mutation sites, including V281A, V281A, P309L, S318G, and D232V. The results showed that the expression of the optimized mutant enzyme also increased by 22±2% compared to the unoptimized enzyme and the optimal reaction temperature of the mutant enzyme lac2-9 was 5 ℃ higher than that of the rlac1338, and the optimal pH increased by 0.5 units. The thermal stability and pH stability of mutant enzyme lac2-9 were also improved. With ABTS as the substrate, the kcat/Km of rlac1338 and mutant strain lac2-9 are the largest than other substrates, 0.1638 and 0.618 s-1M-1, respectively, indicating that ABTS is the most suitable substrate for the recombinant enzyme and mutant enzyme. In addition, the Km of the mutant strain lac2-9 (76 μM) was significantly lower, but the kcat/Km (0.618 s-1M-1) was significantly higher, and the specific enzyme activity (79.8 U/mg) increased by 3.5 times compared with the recombinant laccase (22.8 U/mg). The dye degradation results showed that the use of rlac1338 and lac2-9 alone had no degradation effect on the industrial dyes (indigo, amaranth, bromophenol blue, acid violet 7, Congo red, coomassie brilliant blue (G250)), however, adding small molecular mediators Ca2+ and ABTS at the same time can significantly improve the degradation ability. Compared to the rlac1338,the degradation rates with the simultaneous addition of Ca2+ and ABTS of mutant enzyme lac2-9 for acid violet 7, bromophenol blue and coomassie brilliant blue significantly improved by 8.3;3.4 and 3.4 times.Therefore,the results indicated that the error-prone PCR was a feasible method to improve the degradation activity of laccase for environmental pollutants,which provided a basis for the application of laccase on dye degradation and other environmental pollutants.